Inequalities in provision of the Disability Living Allowance for Down syndrome. Issue 1 (7th March 2007) - Ellis, Jill; Logan, Stuart; Pumphrey, Rachel; Tan, Hooi Kuan; Henley, William; Edwards, Vanessa; Moy, Robert; Gilbert, Ruth
Abstract : Objectives: To assess factors associated with granting of the Disability Living Allowance (DLA) for Down syndrome. Design: Cross-sectional survey. Setting: Families with a child with Down syndrome enrolled in a community-based trial of vitamin supplementation. Participants: 156 children with trisomy 21 (59% male, 20% non-white) were enrolled before 7 months of age and 138 completed follow-up. Main outcome measures: Before the child was 2 years old, we surveyed parents about applications for the DLA and socioeconomic factors, and assessed the child's development. Results: Application for the DLA was not associated with ethnicity or speaking English. Significantly fewer ethnic minority parents (OR = 0.10; 95% CI 0.03 to 0.35; 69% vs 96%, risk difference 27%) and parents with English as a second language (OR = 0.15: 95% CI 0.04 to 0.62; 67% vs 93%, risk difference 26%) were granted the DLA. Amongst those granted the DLA, ethnic minority families were significantly less likely to be granted a higher monetary award (OR = 0.19; 95% CI 0.06 to 0.55). Severity of disability, reflected by quartile of Griffiths Developmental Quotient or the presence of severe cardiac disease requiring surgery, was not associated with application, granting or level of the DLA award. Conclusions: Although all children with Down syndrome meet some of the criteria for the DLA, only 80% were receiving this benefit. The decision to award the DLA and the monetary level of the award favoured white, English speaking parents and was not related to severity of disability. Routine monitoring of awards by ethnicity and language spoken is needed. Trial registration number: NCT00378456.